EXPERIENCE AND PROBLEMS IN THE DEVELOPMENT AND IMPLEMENTATION I&C OF CCPP AT POWER PLANTS OF RUSSIA AND BELARUS - A. D. Melamed; I. Z. Chernomzav; G. S. Peka (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
Summed up the experience of the development and implementation I&C of CCPP by the company «Interavtomatika» AG on various types of CCPP. For example, the I&C of 65 Mw CCPP Borisov (Belarus) CHP considered actual problems of modern I&C of CCPP, among which the first is the integration software of the various local PLC groups processing equipment and PLC unit in a unified system of unit management.